Seismic strengthening of an under-designed RC structure with FRP. - Di Ludovico, M. (Earthquake engineering & structural dynamics.)
The opportunities provided by the use of fiber-reinforced polymer (FRP) for the seismic retrofit of existing reinforced concrete (RC) structures were assessed on a full scale three story framed structure. The structure, designed only for gravity loads, was subjected to a bi-directional pseudo-dynamic (PsD) test at peak ground acceleration (PGA) equal to 0.20 g at the ELSA Laboratory of the Joint Research Centre. The seismic deficiencies exhibited by the structure after the test were confirmed by post-test assessment of structural seismic capacity performed by nonlinear static pushover analysis implemented on the lumped plasticity model of the structure. In order to allow the structure to withstand 0.30 g PGA seismic actions, a retrofit using glass fiber reinforced polymer (GFRP) laminates was designed . The retrofit design was targeted to achieve a more ductile and energy dissipating global performance of the structure by increasing the ductility of columns and preventing brittle failure modes. Design assumptions and criteria along with nonlinear static pushover analysis to assess the overall capacity of the FRP-retrofitted structure are presented and discussed. After the retrofit execution, a new series of PsD tests at both 0.20 g and 0.30 g PGA level were carried out. Theoretical predictions are compared with the main experimental outcomes to assess the effectiveness of the proposed retrofit technique and validate the adopted design procedures.